Flexural Performance of Steel Reinforced ECC-Concrete Composite Beams Subjected to Freeze-Thaw Cycles - Ge, Wenjie; Ashour, Ashraf F.; Lu, Weigang; Cao, Dafu (International journal of concrete structures and materials, 2020)
Experimental and theoretical investigations on the flexural performance of steel reinforced ECC-concrete composite beams subjected to freeze–thaw cycles are presented in this paper. Four groups of reinforced composite beams with different ECC height replacement ratios subject to 0, 50, 100 and 150 cycles of freeze–thaw were physically tested to failure. Experimental results show that the bending capacity decreases with the increase of freeze–thaw cycles regardless of ECC height replacement ratios. However, the ultimate moment, stiffness and durability of ECC specimens and ECC-concrete composite specimens are greater than those of traditional concrete specimens, owing to the excellent tensile performance of ECC materials. With the increase of ECC height, the crack width and average crack spacing gradually decrease. According to materials’ constitutive models, compatibility and equilibrium conditions, three failure modes with two boundary failure conditions are proposed. Simplified formulas for the moment capacity are also developed. The results predicted by the simplified formulas show good agreement with the experimental moment capacity and failure modes. A parametric analysis is conducted to study the influence of strength and height of ECC, amount of reinforcement, concrete strength and cycles of freeze–thaw on moment capacity and curvature ductility of ECC-concrete composite beams.